(untitled) (LACCEI, 2024)
Abstract — This document proposes the calculation of Hemeroby in Peru, examining the levels of relation of Hemeroby with the departmental factors of regional naturalness in the 24 Departments of Peru. The methodology used considers the data from the National Institute of Statistics and RapidEyeTM satellite images corresponding to the year 2019. Pearson statistical analysis, ANOVA and regression analysis were used as statistics. The article shows that the Departments with the highest Hemeroby in Peru are San Martín (57.93), Lambayeque (57.65), while those with the lowest Hemeroby are Moquegua (44.07), Ica (45.24). The mean of Hemeroby in Peru is 53.28 with a calculated error deviation of 0.878. A strong positive correlation between the variable "Natural pasture area / departmental area" and the variable " Altitude of the capital of the Department" (CC = .818, p .001) and, with the variable "Differential of the psychometric fan" (CC = .838, p .001) were found. Also founded a positive correlation between the variable "Altitude of the capital of the Department" and the variable "Differential of the psychometric range" (CC = .877, p .001) This research serves as a platform to identify critical points of increasing anthropogenic influence in rapidly developing regions of Peru.